Current Research Trends In Wire Electrical Discharge Machining (WEDM): A Review - Abdul Rahim, Mohd Aidil Shah; Minhat, Mohamad; Hussein, Nur Izan Syahriah (Penerbit UTeM, 2018)
Wire Electrical Discharge Machine (WEDM) is a ‘non-traditional machining process’ and becoming more important in providing a non-contact machining process which is suitable for machining geometrically complex and hard advanced material which impossible to machine by conventional machine. This paper reviews the experimental investigation results on performance evaluation of machining parameters which effect machining performance which will reflect the machining factors and responses. In addition, the method in analyzing, modelling, development and tool steel in WEDM were also discussed. Last but not least, some recommendations and future WEDM research were propose